Read me. : 10 lessons for writing great copy - Horberry, Roger; Lingwood, Gyles (Londres Laurence King, 2015)
If you've ever struggled to craft a powerful message that really hits the spot, you'll know it's harder than it looks. Wouldn't it be helpful to have an expert on hand to explain how the professionals really do it? Better still, how about a whole range of writers ready to pass on their trade secrets? Well that's exactly what you'll find in the pages of this book. Think of it as a rocket-assisted launch for your writing career, structured over ten distinct lessons and illustrated with classic and contemporary international examples of the best copywriting. Designed to help anyone who works with words improve their writing, this book is packed with practical techniques and features effective exercises to pump up your persuasive powers. Includes inspiring contributions from professional writers, an in-depth look at the challenges involved in writing copy for brands and worked examples that cover writing for digital, brand storytelling and packaging copy.
Keywords: Publicidad -- Redacción